The mitochondrial genome and phylogenetic position of a marine snail Nerita (Heminerita) japonica (Gastropoda: Neritimorpha: Neritidae) - Hiroaki Fukumori; Hajime Itoh; Nobuyoshi Nakajima; Yasunori Kano (Mitochondrial DNA. Part B. Resources, 2020)
The mitochondrial genome of the neritid snail Nerita (Heminerita) japonica (Mollusca: Neritimorpha) from Kumamoto, Japan was determined by whole-genome sequencing. This mitogenome is comprised of 13 protein-coding genes, 2 ribosomal RNA (12S and 16S) genes, and 22 transfer RNA genes, with the same gene order as in the other species of the family Neritidae. A likelihood-based phylogenetic reconstruction recovered the subgenus Heminerita (including N. japonica as its type and N. yoldii from China) as monophyletic and sister to a clade with four species of the subgenera Nerita and Theliostyla.